THERAPEUTIC ARCHITECTURE IN CAFÉ BUILDINGS AS GEN Z’S PREFERRED HEALING PLACE IN DENPASAR - Cokorda Istri Arina Cipta Utari; Km. Deddy Endra Prasandya; Putu Gede Wahyu Satya Nugraha (Architectural Research Journal, 2024)
The number of people with mental disorders in Indonesian teenagers is very high. Bali itself is ranked fourth in the number of people with severe mental disorders in Indonesia, with Denpasar City being the city with the highest prevalence of depression in Bali, which targets Gen Z. Gen Z tends to feel that they need a place where they can go to relieve stress and relax, spend time alone or socialize with friends. Public spaces such as cafes can be used to mingle, spend free time and have fun are now increasingly popular with Gen Z. This study aims to determine the condition of the elements that form cafes in Denpasar regarding therapeutic architecture indicators. The concept of therapeutic architecture is considered to be able to reduce the prevalence of depression because it can provide a pleasant psychological effect for building users. The research method used is quantitative, where quantitative data comes from the results of cafe building users' assessments of the cafe's therapeutic architecture indicators. Quantitative data will then be analyzed with the help of JMP software. The results of the study concluded that several elements form cafes need to be adjusted and accommodated to accommodate the concept of therapeutic architecture to reduce the prevalence of depression in Gen Z.